2020
DOI: 10.1093/ageing/afaa191
|View full text |Cite
|
Sign up to set email alerts
|

Virtual geriatric clinics and the COVID-19 catalyst: a rapid review

Abstract: Background During the current COVID-19 health crisis virtual geriatric clinics have become increasingly utilised to complete outpatient consultations, although concerns exist about feasibility of such virtual consultations for older people. The aim of this rapid review is to describe the satisfaction, clinic productivity, clinical benefit, satisfaction and costs associated with the virtual geriatric clinic model of care. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 28 publications
4
89
0
2
Order By: Relevance
“…This has been further shown during the pandemic, as the group with the highest adoption of telemedicine use has been those aged 20–44, despite the fact that the elderly population generally have the highest yearly number of doctor and hospital visits ( 53 , 54 ). Although there have been some recent efforts to create virtual geriatric clinics to support the elderly during the pandemic, research has shown these have had varying success, and have been met with a variety of problems related to difficulties with technology use ( 55 ). Therefore, despite being the group most in need of telehealth solutions, the elderly community has benefited from their implementation the least.…”
Section: The Effects Of Covid-19 On the Elderly Populationmentioning
confidence: 99%
“…This has been further shown during the pandemic, as the group with the highest adoption of telemedicine use has been those aged 20–44, despite the fact that the elderly population generally have the highest yearly number of doctor and hospital visits ( 53 , 54 ). Although there have been some recent efforts to create virtual geriatric clinics to support the elderly during the pandemic, research has shown these have had varying success, and have been met with a variety of problems related to difficulties with technology use ( 55 ). Therefore, despite being the group most in need of telehealth solutions, the elderly community has benefited from their implementation the least.…”
Section: The Effects Of Covid-19 On the Elderly Populationmentioning
confidence: 99%
“…During the COVID-19 pandemic, numerous health-related rapid reviews have been published. Examples include rapid reviews of clinical swallowing assessments (Bolton et al 2020), virtual geriatric clinics for outpatient consultations (Murphy et al 2020) and palliative care and hospice services (Etkind et al 2020). These reasons justify the authors' use of the rapid review method for the current study.…”
Section: Introductionmentioning
confidence: 99%
“…2020), virtual geriatric clinics for outpatient consultations (Murphy et al . 2020) and palliative care and hospice services (Etkind et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of telemedicine clinics reduced the risk of transmission of the virus, while also ensuring adequate provision of outpatient care. Virtual clinics have grown in popularity during the COVID-19 pandemic (17) and are largely touted as an e cient means of delivering care to fracture clinic patients and to older adults (18,19). Data from patient cohort demonstrates satisfactory outcomes from the clinic with 64% of the cohort being discharged without the need for further follow-up.…”
Section: Discussionmentioning
confidence: 99%